2014
DOI: 10.1002/hed.23730
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery for recurrent carcinoma of the cervical esophagus postesophagectomy

Abstract: Background Management of cervical esophageal tumor postesophagectomy is mainly palliative because of inadequate exposure of tumor in the cervicothoracic region. In this study, we propose a means of cure for these patients. Methods Between January 2003 and June 2013, 6 patients underwent curative pharyngolaryngectomy and completion cervical esophagectomy via manubrial resection. Operative outcomes were analyzed and compared with a historical cohort who received palliative therapy. Results One patient required p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The esophagus was transected 3 cm distal to the inferior-most border of the tumor. 7 Regional nodal dissection was not routinely performed in the absence of confirmed nodal metastasis. For patients with confirmed cervical nodal metastasis, ipsilateral levels II to IV and VI nodal stations were removed.…”
Section: Methodsmentioning
confidence: 99%
“…The esophagus was transected 3 cm distal to the inferior-most border of the tumor. 7 Regional nodal dissection was not routinely performed in the absence of confirmed nodal metastasis. For patients with confirmed cervical nodal metastasis, ipsilateral levels II to IV and VI nodal stations were removed.…”
Section: Methodsmentioning
confidence: 99%
“…However, since resection and reconstruction of the trachea and esophagus each presents with a unique set of challenges, the difficulty and risk of combined tracheal and esophageal reconstruction rise exponentially (Ng, 2015). Not only the complexities of tracheal This paper was presented at the 9th Congress of World Society for Reconstructive Microsurgery (WSRM 2017), Seoul, Korea, 2017. reconstruction but also difficulties associated with digestive tract reconstruction (e.g., anastomotic leakage from the reconstructed digestive tract) inevitably increase the incidence of mediastinitis and mortality (Chow, Chan, & Wei, 2015). Ghali et al (2015) reported that the goals of reconstruction for combined tracheal and esophageal defects are (1) to provide a secure airway, (2) to achieve reliable coverage of major blood vessels, and (3) to restore the continuity of the digestive tract.…”
Section: Introductionmentioning
confidence: 99%